Leader Sex and Employee Power Distance Orientation as Boundary Conditions of the Relationship between Leader Humility and Leader-Member Exchange. Issue 5 (20th October 2021) - Wang, Peng; Dust, Scott; Wang, Zhen
ABSTRACT: This study draws upon social information processing theory to investigate two boundary conditions of the effect of leader humility on follower perceptions of leader-member exchange, namely, leader sex and employee power-distance orientations. Using 496 supervisor-employee dyads from China, we find a positive relationship between leader humility and follower perceptions of leader-member exchange, and confirm the moderating effects of leader sex and employee power-distance orientations. Specifically, the positive relationship between leader humility and follower perceptions of leader-member exchange is enhanced for male leaders but diminished for female leaders, and is also stronger for employees who have lower power-distance orientations. Theoretical and practical implications are discussed.